Advanced Core–Shell Nanoparticle Catalysts for Efficient Organic Transformations. Issue 7 (12th March 2013) - Mitsudome, Takato; Kaneda, Kiyotomi
Abstract With the advent of nanotechnology, the rational design of core–shell nanoparticle catalysts has attracted enormous attention. This Minireview describes recent progress in designs of state‐of‐the‐art core–shell nanostructured catalysts with active species in the core for efficient organic transformations. These core–shell catalysts demonstrate high potential for excellent durability against aggregation due to the encapsulation process as well as unique functionalities for different purposes such as magnetic properties for easy separation, porous shell adjustability for shape selectivity, stimuli responsiveness and strong metal–support interaction for high chemoselectivity, and site isolation for the development of one‐pot catalysts.